2012
DOI: 10.3141/2320-07
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Neighborhood Crime on Mode Choice

Abstract: It is understood that the threats posed by possible criminal activity in a neighborhood can play a major role in the decision to drive, take transit, walk, or ride a bicycle, but little empirical evidence has yet been gathered to support this notion, let alone guide public infrastructure investments, land use planning, or the allocation of police services. This study found that high-crime neighborhoods tend to discourage residents from walking or riding a bicycle. When a high-crime neighborhood is compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 12 publications
(8 reference statements)
1
17
0
Order By: Relevance
“…Utilitarian bicycling was positively associated with individuals' perceived number of recreation destinations in the home neighborhood (Beenackers et al 2012) and with bars and drinking establishments , and bicycling for all purposes was positively associated with the number of office/fast food/hospitals and the perceived presence of grocery shops and schools at the home neighborhood level (Vernez-Moudon et al 2005). Bicycle mode choice was positively associated with educational uses at destinations (Winters et al 2010), an origin accessibility to retail and services index for recreation trips (Rajamani et al 2003), and a transit accessibility measure at the household TAZ for commuting trips (Ferrell and Mathur 2012). However, these results do not hold across other studies.…”
Section: Land Usementioning
confidence: 96%
See 4 more Smart Citations
“…Utilitarian bicycling was positively associated with individuals' perceived number of recreation destinations in the home neighborhood (Beenackers et al 2012) and with bars and drinking establishments , and bicycling for all purposes was positively associated with the number of office/fast food/hospitals and the perceived presence of grocery shops and schools at the home neighborhood level (Vernez-Moudon et al 2005). Bicycle mode choice was positively associated with educational uses at destinations (Winters et al 2010), an origin accessibility to retail and services index for recreation trips (Rajamani et al 2003), and a transit accessibility measure at the household TAZ for commuting trips (Ferrell and Mathur 2012). However, these results do not hold across other studies.…”
Section: Land Usementioning
confidence: 96%
“…Some have found a significant but modest positive effect of population density on bicycle commute mode choice (Rybarczyk and Wu 2013) and levels of use (Beenackers et al 2012), while many more have not found any relationship with population density (Frank et al 2008;Schneider 2011;Cervero et al 2009;Rajamani et al 2003;Winters et al 2010;Zhao 2014). Ferrell and Mathur (2012) found a negative relationship between population density in the destination TAZ and bicycle mode choice for work and non-work trips. Employment density has been less studied.…”
Section: Land Usementioning
confidence: 99%
See 3 more Smart Citations